Supply Chain Environmental Uncertainty, Competitive Advantage, and Operational Performance in Manufacturing Industry - La Hatani; Nursaban Rommy; Usman (Brazilian Journal of Operations & Production Management, 2024)
Goal: This study investigates the impact of Supply Chain Environmental Uncertainty (SCEU) on competitive advantage and operational performance in manufacturing companies. The mediating role of competitive advantage and the moderating role of supply chain environmental uncertainty in the relationship between competitive advantage and operational performance were examined.